Spontaneous scrotal faecal fistula: A rare complication of incarcerated inguinal hernia in infancy - Sowande O; Adejuyigbe O; Ogundoyin O; Uba A; Chinda J (Wolters Kluwer Medknow Publications, 2006)
Spontaneous scrotal faecal fistula is a rare complication of incarcerated inguino-scrotal hernia in the neonate and infants. Only five previous cases have been reported in the English medical literature. We report another case of a 28-day-old neonate, who presented with fecal fistula following prolonged incarceration of a right inguino-scrotal hernia. The etiology and management of this rare complication is discussed.